Effects of Slope on Soil Properties in The Rangeland of Southern Al-Jabal Al -Akhdar Region, Northeastern Libya - Hameda Moftah,; Sana Muhy El Din,; Adel Mahmoud,; Fathi Lamloum,; Alnaji Ahmida, (AlQalam Journal of Medical and Applied Sciences, 2023)
Aims. This study was conducted on southern slope of Al-Jabal Al-Akhdar, Libya to estimate some soil properties, and to study effects of slope on those properties. Methods. Twelve sites were selected. Slope in the study area was divided into three levels (high slope, medium slope and low slope). Soil samples were collected for each site and analyzed in laboratory. We applied LFA technique to assess soil surface condition. One-way ANOVA (LSD test) was applied, where slope is independent factor and soil properties are dependent variables. Results. The results did not show any significant differences between soil properties, except for soil PH and calcium carbonate. Also, there were no significant differences between the means of soil surface indices except for SSCI. Our results confirmed that the effect of slope became significant when its rate exceeds 10%, for this reason, most of the statistical differences between soil properties means were insignificant in our study, as the highest rate of slope in the study area is 7%. Conclusion. It is necessary to conduct future studies to cover a larger area in the region for a comprehensive understanding about soil properties at the local level, and thus knowing the proper ways to maintain and benefit from it.